The effectiveness of provision of new static information signage: a case study of International Islamic University Malaysia, Gombak campus - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (Malaysian Institute of Planners, 2012)
In Malaysia, the provision of road and highway traffic signage on public roads has been regulated by the Department of Works and Departments of Road Transport Acts, Rules and Regulations. Many studies have concentrated on the responses and impacts of these types of signage. However, in many other private roads which are not regulated under these Acts,Rules and Regulations, several non-conventional types of signages have been provided. There is a lack of study, however, on the impacts of and drivers’ responses towards these signage. The study, hence, explore the types, contents and locations of these signage. Additionally, the impacts of and responses towards these signage are evaluated in a controlled campus environment. Using the International Islamic University Malaysia’s young student drivers as the unique purposive samples, statistical tests including multiple regression and chi-square analyses have been conducted. It is preliminary reported that gender, luminacy, and observation frequency, to a certain extent, influenced drivers’ responses towards the information conveyed by the signage.